Evaluation of the Clinical Utility of Factor V, VII, and VIII Assays in Assessment of DIC. (11th September 2019) - Carll, Timothy; Mikrut, Krzysztof; Wool, Geoffrey
Abstract: Disseminated intravascular coagulation (DIC) is a hematologic emergency that requires prompt diagnosis and intervention. The International Society of Thrombosis and Hemostasis (ISTH) has developed a scoring system to diagnose life-threatening DIC, which is based upon routine coagulation lab assays, including PT, D-dimer, fibrinogen, and platelet count. Laboratory assays for coagulation factors V (FV) and VII (FVII) are commonly used to evaluate for abnormal liver function in patients with abnormally elevated PT/INR. They are also frequently ordered as part of workup for DIC, in combination with factor VIII (FVIII), at UChicago Medicine. However, these coagulation factors are not part of the guideline-based DIC workup, and their utility in the evaluation of DIC is not clearly defined. A retrospective review of orders containing at least factors V, VII, and VIII was performed at UChicago Medicine ranging from December 1, 2016, through November 30, 2017. Results for corresponding coagulation lab results, anticoagulation therapy, and factor-replenishing therapy (vitamin K, plasma, cryoprecipitate, and factor concentrates) were pooled. Patient charts were reviewed for DIC diagnosis by clinical suspicion (defined by keyword searches of clinician documentation) and by ISTH scoring. In total, 117 patients were reviewed. Only 47 had complete coagulation data to perform ISTH scoring. Of these, 30 met ISTH criteria for DIC (64%). No patient was diagnosed with DIC based on abnormal coagulation factor assays in the absence of abnormal screening coagulation results. The most common underlying diagnosis in those meeting ISTH criteria was sepsis. A statistically significant lower FV level was observed in those meeting ISTH criteria ( P < .001, one-tail), but no such differences were observed in FVII or FVIII levels ( P = .059, .224). FVIII was only reduced in 2 of the 117 reviewed patients (2%), and FVIII levels were rarely repeated to trend for any decrease in FVIII levels. FVII was reduced in 88 patients, of which 57 also showed reduced FV levels. Twenty-eight patients received factor replenishing therapy shortly before their initial lab draw for factor testing. Of the 88 patients with reduced FVII, 61 received factor-replenishing therapy within 3 days following the lab draw. We concluded that at this institution, factor level assays are often ordered without first obtaining complete screening coagulation assays, which represents poor utilization of laboratory resources due to cost and time constraints placed by factor assay testing. Factors VII and VIII are ineffective at evaluation of DIC, and factor VIII levels as currently utilized are of particularly little value given its near-universal elevation in the inpatient setting and lack of repeat testing for trend. We also took this opportunity to review the clinical response to abnormal testing results and found that the majority of abnormal factor testing results in the reviewed setting prompted therapeutic correction.